Atmospheric Triggers of the Brunt Ice Shelf Calving in February 2021. Issue 11 (31st May 2022) - Francis, Diana; Fonseca, Ricardo; Mattingly, Kyle S.; Marsh, Oliver J.; Lhermitte, Stef; Cherif, Charfeddine
Abstract: The calving of Antarctic ice shelves remains unpredictable to date due to a lack of understanding of the role of the different climatic components in such events. In this study, the role of atmospheric forcing in the calving of the Brunt Ice Shelf (BIS) in February 2021 is investigated using a combination of observational and reanalysis data. The occurrence of a series of extreme cyclones around the time of the calving induced an oceanward sea‐surface slope of >0.08° leading to the calving along a pre‐existing rift. The severe storms were sustained by the development of a pressure dipole on both sides of the BIS associated with a La Niña event and the positive phase of the Southern Annular Mode. Poleward advection of warm and moist low‐latitude air over the BIS area just before the calving was also observed in association with atmospheric rivers accompanying the cyclones. Immediately after the calving, strong offshore winds continued and promoted the drift of the iceberg A‐74 in the Weddell Sea at a speed up to 700 m day −1 . This study highlights the contribution of local atmospheric conditions to ice‐shelf dynamics. The link to the larger scale circulation patterns indicates that both need to be accounted for in the projections of Antarctic ice shelf evolution. Plain Language Summary: A calving event is the process by which a large block of ice gets separated from an ice shelf or glacier and forms an iceberg. Large calving events from marine‐terminating ice shelves around Antarctica remain to date highly unpredictable. This process is typically associated with the glaciological cycle of the ice shelves as well as ocean dynamics. However, atmospheric forcing in triggering such events has been largely overlooked. This is investigated for the calving of iceberg A‐74 from the Brunt Ice Shelf (BIS) in February 2021. We found that strong near‐surface winds associated with intense cyclones promoted the event via an increased sea‐surface slope toward the open ocean, which amplified the stress on the pre‐existing rift and led to the calving. After the calving, the iceberg drifted westwards in the Weddell Sea at a speed of 700 m day −1 aided by strong offshore winds. The extreme weather conditions leading to the calving were associated with an alternation of a series of high (blockings) and low (troughs) pressure systems around the BIS region. Key Points: An intense and stationary cyclone around the ice shelf, which was part of a wave train occurred at the time of the calving Strong near‐surface winds associated with the cyclone promoted the calving of the Brunt Ice Shelf via oceanward sea‐surface slope Calving occurred on 26 February when the ice accelerated significantly in a westward direction from a velocity of 4–6 to 700 m day −1